New heaven and new earth : prophecy and the millennium : essays in honour of Anthony Gelston - Gelston, A.; Harland, P. J.; Hayward, Robert, 1948- (Supplements to Vetus Testamentum, 1999)
This volume is a collection of essays on prophecy and apocalyptic, and is compiled in honour of Anthony Gelston. The theme has been chosen to coincide with the dawn of the new millennium in the year 2000. The essays examine the following: Balaam's oracles in Numbers, Philo and the Aramaic Targums; the future in the Books of Chronicles; Job 19:25; the shape of the Psalter; Isaiah 11:6-9; Isaiah 51:6; the value of human life in Ezekiel; Calvin, Pusey and Robertson Smith's commentaries on Hosea; Qoheleth, Hosea and attribution in biblical literature; the social background of Malachi; apocalyptic and early Jewish wisdom literature; Judith, Tobit, Ahiqar and History; 1 Corinthians 15:54; Revelation 4-5; the writings of Aphrahat, Šubḥalmaran, George Stanley Faber and Cotton Mather.